2022
DOI: 10.1021/acs.inorgchem.1c03786
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Coordination Modes of Multidentate Neutral Amine Ligands with Group 1 Metal Cations

Abstract: This work comprehensively investigated the coordination chemistry of a hexa -dentate neutral amine ligand, namely, N,N′,N” - tris -(2- N -diethylaminoethyl)-1,4,7-triaza-cyclononane (DETAN), with group-1 metal cations (Li + , Na + , K + , Rb + , Cs + ). Versatile coordination modes were observed, from four-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…The other key fragment of the DETAN ligand is its TACN-based macrocycle backbone. The SCXRD solid-state structures 15 of 1 -Li/Na and 2 -Li/Na suggested that the N → M dative bonds in the macrocycles are much shorter compared to those in the sidearms (Δ N⃗M : ∼0.4 Å), indicating that the macrocycle is the structural dictating group, while the sidearms act as weakly bonded hemilabile pendant groups. To prove this hypothesis, the coordination behaviors of the macrocycle and the sidearms must be disentangled and studied separately.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The other key fragment of the DETAN ligand is its TACN-based macrocycle backbone. The SCXRD solid-state structures 15 of 1 -Li/Na and 2 -Li/Na suggested that the N → M dative bonds in the macrocycles are much shorter compared to those in the sidearms (Δ N⃗M : ∼0.4 Å), indicating that the macrocycle is the structural dictating group, while the sidearms act as weakly bonded hemilabile pendant groups. To prove this hypothesis, the coordination behaviors of the macrocycle and the sidearms must be disentangled and studied separately.…”
Section: Resultsmentioning
confidence: 99%
“…Complex 4 was reported in our previous work. 15 The solid-state SCXRD structures of 3 and 4 ( 15 ) feature pseudo - C 3 v symmetries ( Figure 8 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We would advocate that it is now considered vital to include the whole of group 1 (Li ‐ Cs) when investigating catalytic performance, since gradations in reactivity can take place depending on which alkali metal is used. Investigations to gain more structural insights in whole series of group 1 complexes often exclude the heavier homologues due to the synthetic challenge or inaccessibility, [42,43] hence studies such as that by Schulz, [44] Roesky, [45] or Liddle, [46] in which light is shed on the whole of group 1 within the same ligand framework, remain exceptional. One of the most widely utilized ligands to study alkali metals in complexes are amide derivatives since they are of central importance in many chemical transformations as metallation and amide‐transfer reagents or as Brønsted bases [47–49] .…”
Section: Introductionmentioning
confidence: 99%
“…However, this route has not been explored so far. In this context and based on our interest in lithium chemistry [23]- [25], we hypothesized that by introducing lithium metal as a reductant and a Li-ion source, and using mechanochemical methods to increase the reducibility of Co3O4, it is possible to deliver facile Co3O4 reduction and Li + doping in a one-pot manner. The findings are reported herein.…”
mentioning
confidence: 99%